Theoretical Considerations of Interdisciplinary Expertise in Traffic - Peran, Zdravko; Županović, Ivan; Jelušić, Frane (Promet - Traffic&Transportation, 2012)
Jnterdisciplinwy traffic expertise is being increasingly appliedin road traffic. It is not possible to determine whether anaccident had been intentionally set up without such expertise.The interdisciplinary expertise is the result of mutual work ofseveral different interdisciplinary experts. The paper analysesthe basic characteristics of interdisciplinary investigation ofset-up traffic accidents. Special attention has been paid to interdisciplinwyexpertise of set-up traffic accidents involving injuredpersons or fatalities.